Once-monthly continuous erythropoietin receptor activator (CERA) for haemoglobin maintenance in haemodialysis patients with chronic renal anaemia - Duman, Neval; Uyanik, Abdullah; Unsal, Abdulkadir; Sezer, Siren; Camsari, Taner; Cirit, Mustafa; Ozdener, Fatih (Oxford Univ Press, 2014)
Background. This study was conducted to evaluate the efficacy and safety of once-monthly continuous erythropoietin receptor activator (CERA) for maintenance of stable haemoglobin (Hb) levels in adult chronic renal anaemia patients on dialysis according to local clinical judgment in Turkey. Methods. This was a prospective, open-label, single-arm, multi-centre study conducted in 20 centres in Turkey. After a 4-week screening period, eligible patients receiving conventional erythropoiesis-stimulating agents were converted to monthly intravenous CERA and entered a 16-week CERA dose-titration period (DTP) followed by an 8-week efficacy evaluation period (EEP) and a 4-week safety follow-up. The primary endpoint was the proportion of patients whose Hb concentration remained stable within +/- 1.0 g/dL of their reference Hb and within the range of 10.0-12.0 g/dL during the EEP. Results. A total of 173 patients were screened, 132 entered the DTP and 84 completed the study. Thirty-nine patients [46.4%(95% confidence interval: 35.5-57.7%)] maintained stable target Hb concentrations. The mean change in time-adjusted average Hb concentration was 0.29 +/- 1.08 g/dL between baseline and the EEP. The mean CERA monthly dose was 112.4 +/- 76.78 mu g during the EEP, and the CERA dose was adjusted in 39 patients (36.4%). Eleven patients (8.4%) reported 13 treatment-related adverse events, the most frequent adverse events being infections and infestations, gastrointestinal and vascular disorders. Conclusions. Once-monthly CERA maintains stable Hb concentrations in chronic renal anaemia patients on dialysis in Turkey. The study results confirm the known efficacy and safety profile of CERA.
Keywords: anaemia; dialysis; erythropoietin receptor; kidney disease